Optimalisasi Pelatihan Dakwah Kampus dalam Mencetak Kader Da’i di Institut Teknologi Bandung (ITB) - Nopitasari, Irma; Sarbini, Ahmad; Anwar, Saeful (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to determine the analysis of conditions in determining training plans, optimizing strategic plans and implementing efforts to produce da'i cadres at the GAMAIS ITB Campus Da'wah Institute. This study uses a descriptive method with a qualitative approach. Based on the results of research conducted at LDK GAMAIS ITB from optimizing campus da'wah training in producing da'i cadres, it can be concluded: First, that the analysis of da'wah training conditions at LDK GAMAIS ITB is divided into seven parts viewed from various conditions. Second, the da'wah training strategy plan at LDK GAMAIS ITB is a follow-up to the condition analysis. With this strategic plan, it can be a reference for the implementation of LDK GAMAIS ITB da'wah training. Third, the results and efforts to implement training at LDK GAMAIS ITB which produce an effective and efficient network model.